Kelor Berdaya: Strategi Pengembangan UMKM Berbasis Potensi Lokal - Ratnawati; , Maryana; Tri Wahyuningsih; Nurul Annisa; Khoirul Norma Rahayu (Jurnal Pengabdian Masyarakat: Tipis Wiring, 2026)
MSMEs in Gunungkidul Regency have significant potential to drive the local economy, but they still face various structural obstacles, such as limited capital, low production technology, weak product branding and packaging, and the suboptimal utilization of local potential as a competitive advantage. Furthermore, the lack of a sustainable mentoring program from the local government hinders MSMEs' full development. MSMEs play a crucial role in creating jobs, reducing poverty, and increasing community empowerment. The success of the mentoring program in Kelor Village demonstrates that integrated mentoring can improve production quality, financial management, and market access for MSMEs. Based on these conditions, the Gunungkidul Regency Government needs to implement an Integrated MSME Mentoring Model consisting of five main pillars: the establishment of mentoring units and MSME empowerment centers in each village, the provision of appropriate technology and a shared facility center, regular training and product certification facilitation, the holding of MSME Expos and collaboration with digital marketplaces, and a regular monitoring system with measurable indicators. The implementation of this policy is expected to increase MSME competitiveness, expand markets, and support sustainable regional economic development. On the other hand, if it is not implemented immediately, MSMEs will continue to stagnate, lose out to products from outside the region, and fail to take advantage of the rapidly growing digital economic opportunities